Measurement of Nuclear Reaction Cross Sections for Applications in Radiotherapy with Protons, Helium and Carbon Ions - Horst, Felix Ernst; Justus Liebig University Giessen (My University, 2019)
This thesis studies nuclear fragmentation induced by protons, 4He and 12C ions in the energy range used for radiotherapy through two different experimental setups. A comprehensive understanding of these nuclear reactions is essential for accurate dose calculation in patients and for verification of the treatment via positron emission tomography (PET). In the first experiment, conducted at the Heidelberger Ionenstrahl-Therapiezentrum, charge- and mass-changing cross sections were measured for the colliding systems 4He +1 H, 4He +12 C, 4He +16 O and 4He +28 Si in the energy range of 70 - 220 MeV/u. The cross sections were obtained via the attenuation method where a DeltaE - E scintillator telescope was used for particle identification. These data will have particular relevance for future applications of 4He ions in ion beam radiotherapy as this technique relies on precise nuclear reaction models for an accurate dose calculation. The widely used parametrization for the total reaction cross section delta R by Tripathi et al. under-predicts the new experimental cross sections for 4He ions in the therapeutic energy range by up to 30%, which can lead to considerable dose calculation uncertainties. Therefore, the parameters in the Tripathi model were optimized and the FLUKA nuclear reaction model was adjusted accordingly. The new models were validated by comparing radiation transport calculations against available 4He depth dose measurements. The impact of the nuclear model changes for 4He ions on their relative biological effectiveness was studied through radiobiological calculations based on the local effect model.In the second experiment, conducted at the Marburger Ionenstrahl-Therapiezentrum, cross sections were measured for the production of 10C, 11C and 15O by protons (40 - 220 MeV) and 12C ions (65 - 430 MeV/u) on C and O targets. The cross sections were obtained via activation measurements of irradiated graphite and BeO targets using a set of three scintillators coupled by a coincidence logic. The measured cross sections are relevant for the particle range verification method by PET where accurate predictions of the beta+-emitter distribution produced by therapeutic beams in the patient tissue are required. This dataset will be useful for validation and optimization of proton-nucleus and nucleus-nucleus reaction models within radiation transport codes. For protons there is a good agreement between a radiation transport calculation using the measured cross sections and a thick target PET measurement from the literature. For 12C-induced nuclear reactions the novel cross sections are a good basis for further model developments.

Die vorliegende Arbeit handelt von Untersuchungen zur Kernfragmentierung induziert durch Protonen, 4He- und 12C-Ionen im zur Strahlentherapie genutzten Energiebereich mittels zweier unterschiedlicher Experimente. Ein umfangreiches Verständnis derartiger Kernreaktionen ist die Voraussetzung für eine genaue Dosisberechnung im Patienten sowie für die Therapie-Verifikation mittels Positronen-Emissions-Tomographie (PET).In der ersten Messreihe, durchgeführt am Heidelberger Ionenstrahl-Therapiezentrum, wurden Wirkungsquerschnitte (Ladungs- und Massenänderung) für die Systeme 4He +1 H, 4He +12 C, 4He +16 O und 4He +28 Si im Energiebereich 70 220 MeV/u bestimmt. Diese Wirkungsquerschnitte wurden mit der Schwächungsmethode ermittelt, wobei ein DeltaE - E Szintillatorteleskop zur Teilchenidentifikation verwendet wurde. Die so gewonnenen Daten haben besondere Relevanz für zukünftige Anwendungen von 4He-Ionen in der Partikeltherapie, da diese Technik auf präzise Kernreaktionsmodelle für eine genaue Dosisberechnung angewiesen ist. Die weit verbreitete Parametrisierung des totalen Reaktionsquerschnitts deltaR von Tripathi et al. unterschätzt die neuen experimentellen Wirkungsquerschnitte für 4He-Ionen im therapeutischen Energiebereich um bis zu 30%, was zu erheblichen Unsicherheiten in der Dosisberechnungs führen kann. Daher wurden die Parameter im Tripathi- Modell sowie das Modell in FLUKA auf Basis der neuen Wirkungsquerschnitte optimiert. Die optimierten Modelle wurden durch den Vergleich von Strahlungstransportrechnungen mit veröffentlichten 4He-Tiefendosismessungen validiert. Die Auswirkungen der Anpassung der nuklearen Modelle für 4He-Ionen auf deren relative biologische Wirksamkeit wurden durch strahlenbiologische Berechnungen auf Grundlage des Local Effect Modells untersucht.In der zweiten Messreihe am Marburger Ionenstrahl-Therapiezentrum wurden Wirkungsquerschnitte für die Produktion von 10C, 11C und 15O durch Protonen (40 - 220 MeV) und 12C-Ionen (65 - 430 MeV/u) an C und O Targets bestimmt. Diese wurden durch Aktivierungsmessungen von bestrahlten Graphit- und BeO-Targets unter Verwendung eines Aufbaus aus drei Szintillatoren, gekoppelt durch eine Koinzidenzlogik, ermittelt. Die gemessenen Produktionsquerschnitte sind für die in-vivo-Reichweitenverifikationsmethode mittels PET relevant. Bei dieser sind genaue Vorhersagen der beta+-Emitterverteilung, die vom therapeutischen Strahl im Patientengewebe erzeugt wird, erforderlich. Auch dieser Datensatz ist nützlich für die Validierung und Optimierung von Proton-Kern- and Kern-Kern-Reaktionsmodellen in Strahlungstransport-Codes. Für Protonen stimmen Strahlungstransportrechnungen unter Verwendung der gemessenen Produktionsquerschnitte gut mit der PET-Messung eines bestrahlten dicken Targets aus der Literatur überein. Für 12C-induzierte Kernreaktionen sind die neu gewonnenen Wirkungsquerschnitte eine gute Grundlage zur Weiterentwicklung von Modellen.
Keywords: ddc:530